Application of Absorbable Suture in Strabismus Correction and Nursing Management Advantage of Watson Care Theory in Perioperative Period. (4th March 2022) - Guo, Weina; Yang, Suling; Gong, Yuexing; Zhang, Lizhi; Jin, Tao; Wang, Jiancang; Guo, Xiting; Sun, Huihui; Song, Yanxia; Tian, Haixia
Abstract : Objectives . The article is aimed at investigating the suture effect of absorbable suture in strabismus correction and the advantage of Watson care theory. Methods . 148 children with strabismus were enrolled in this study and divided into two groups. The control group received routine nursing, and on this basis, the observation group was given Watson care theory nursing and eye muscle suture with absorbable sutures. The degree of cooperation (induction compliance checklist (ICC) score), negative emotion (modified Yale preoperative anxiety scale (m-YAPS) score), pain (face pain scale (FPS) score), quality of nursing management, parents' satisfaction, clinical efficacy, and adverse reactions were compared. Results . After nursing and surgical treatment, all children's strabismus symptoms were improved, and the improvement of strabismus and visual function in the observation group was more obvious. Watson care nursing can effectively improve the nursing management quality, parents' satisfaction, children's negative emotions, and treatment compliance. Conclusions . As a result, Watson care theory nursing is of great significance for improving the relationship between nurses and patients and building a harmonious hospital.